PENGARUH GOOD CORPORATE GOVERNANCE DAN PRIVATISASI TERHADAP KINERJA KEUANGAN (STUDI PADA BUMN YANG TERCATAT DI BURSA EFEK INDONESIA (BEI) TAHUN 2009-2013) - Widya Orin; Zirman -; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the influence of independent directors, independent directors, audit committee and privatization of financial performance (a study on SOEs listed on the Stock Exchange Year 2009 to 2013). Total population in this study which amounted to 10 companies. While the sample in this study using total sampling that the overall population sampled as many as 10 companies. Data used in this research is quantitative data in the form of secondary data collection techniques in the documentation of existing data. This study tested using multiple regression analysis with the help of statistical data processed with SPSS version 21. Classic assumption test which used the heteroscedasticity test, autocorrelation test and multicollinearity. Test hypotheses used the statistical t-test and test the coefficient of determination. These results indicate that the independent commissioner significantly affect financial performance with thitung 5,085> 2,021, independent directors significantly affect financial performance with thitung 3,099> 2,021, the audit committee did not significantly affect the financial performance of the thitung 1,292 <2,021 and privatization significantly affect financial performance with thitung 4,850> 2,021. Adjusted R Square shows the value of 0,571. It shows that 57,1% of financial performance is influenced by variables - determinant variables in the model, while 42,9% is explained by other variables not included in the model.Keywords: independent directors, independent directors, audit committee, privatization and financial performance